Note of Existentialism in the Poetry of Philip Larkin - Uddin, Mohammad Taj (IIUC Studies, 2012)
Existentialism became popular in the twentieth century, and it captured virtually every form of human thought and expression, including the novel, the theatre, poetry, art and theology. Though this philosophy had no specific system or sets of systems, yet it got a wide range of responses due to contemporary social circumstances. Individuals of the 20th century had a problematic existence with anguish, uncertainty, fear, alienation and despair because of different negative socio-political and cultural events that affected every aspect of life in Europe. Philip Larkin belonged to the same century and most of his poems present the typical problems of existence of an individual in the contemporary society. With an aim of better understanding of the poetry of Philip Larkin this paper explores how the poet, while dealing with the themes of his poetry, reflects the mood and ideas of existentialist philosophers. Since philosophy is closely connected with literature, as with other branches of knowledge, this study may help the readers understand Larkins poetry from a new perspective. DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12251 IIUC Studies Vol.6 2010: 97-110